2021
DOI: 10.3390/min11080878
|View full text |Cite
|
Sign up to set email alerts
|

Torque Analysis of a Gyratory Crusher with the Discrete Element Method

Abstract: Comminution by gyratory crusher is the first stage in the size reduction operation in mineral processing. In the copper industry, these machines are widely utilized, and their reliability has become a relevant aspect. In order to optimize the design and to improve the availability of gyratory crushers, it is necessary to calculate their power and torque accurately. The discrete element method (DEM) has been commonly used in several mining applications and is a powerful tool to predict the necessary power requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In studies carried out on crushers that have a conical structure rather than a beam structure, heat treatment [18] was applied on a cone crusher surface to increase the resistance to abrasion. Gyratory crusher torque analysis [19] was analyzed with discrete element method and found that large particles cause to decrease the crushing torque.…”
Section: Methodsmentioning
confidence: 99%
“…In studies carried out on crushers that have a conical structure rather than a beam structure, heat treatment [18] was applied on a cone crusher surface to increase the resistance to abrasion. Gyratory crusher torque analysis [19] was analyzed with discrete element method and found that large particles cause to decrease the crushing torque.…”
Section: Methodsmentioning
confidence: 99%
“…To the knowledge of the authors, there has been no solution reported for online wear monitoring of gyratory crusher liners. Recent advancements in discrete element modelling (DEM) have enabled the simulation of industrial-scale gyratory crushers [15][16][17]. Particle breakage models were developed and incorporated into DEM to study the size reduction process of rock.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the liner's wear life also largely relies on its material selection. Materials with higher abrasion wear resistance, such as high manga- Recent advancements in discrete element modelling (DEM) have enabled the simulation of industrial-scale gyratory crushers [15][16][17]. Particle breakage models were developed and incorporated into DEM to study the size reduction process of rock.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods such as ignoring particle shapes (using only spherical particles), particle upscaling, coarse grain modeling, and periodic simulations have been proposed to reduce the related complexity and computational cost. For example, Moncada et al [19] successfully developed and validated a DEM model to predict the performance of a gyratory crusher. The validation was performed in terms of throughput, crushed particle size, and crushing power and the effects of particle size on power consumption, torque force, and equipment fatigue were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moncada et al [ 19 ] successfully developed and validated a DEM model to predict the performance of a gyratory crusher. The validation was performed in terms of throughput, crushed particle size, and crushing power and the effects of particle size on power consumption, torque force, and equipment fatigue were investigated.…”
Section: Introductionmentioning
confidence: 99%